Synthesis of porous adsorbents for cooling and dehumidification applications - Chan, Jing Ting (Nanyang Technological University, 2020)
Metal-Organic Frameworks (MOFs) are crystalline porous materials made up of a three-dimensional (3D) network of metal ions and organic molecules. In view of their unique characteristics, MOFs as novel adsorbents has been of interest for its usage in industrial applications like cooling and dehumidification applications in the recent years. The features of MOFs are, high porosities, wide surface areas, various topologies, modifiable pore size and functionality. In this report, three types of MOFs are presented, namely, MIL-101(Cr), ILAC-MIL-101(Cr), BMIM-MIL-101(Cr), MIL-125 and MOFs doped with ionic liquid. The experimental techniques employed to synthesis these MOFs were studied. The evaluation of MOFs characteristics was carried out by (i) scanning electron microscopy (SEM) for understanding structural morphology and (ii) thermogravimetric analysis (TGA) for thermal stability of porous adsorbents. Additionally, the water adsorption isotherms and kinetics were measured by the gravimetric methodology. The water adsorption measurements were carried out for the temperatures ranging from 25oC to 60oC and the pressure up to the saturated limit. The results show that the water-vapour transfer per adsorption-desorption periods are found higher with fast kinetics. Therefore, the suggested MOFs as presented in this report are applicable for the design and development of adsorption assisted cooling and dehumidification system.